Perkataan Arab dalam Bahasa Melayu: Satu Tinjauan dari Aspek Semantik - Yusoff, Mohd. Alwee (Jurnal Usuluddin, 2006)
This article attempts to see the use of Arabic words in Malay language from semantic aspect. The use of these words gives rise to misunderstanding to the public especially for those who do not know Arabic language. Changes of Arabic words in Malay language implicate changes in meaning when they are spelled in Malay especially from aspect of grammatical, symbols, thoughts and contexts.